SOME CONSIDERATIONS OF ENGLISH LANGUAGE TEACHING FOR PRIMARY SCHOOLS - Sirajuddin Kamal (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract The Indonesian government has acknowledged the importance of English by putting it into the education system for five decades. English has been integrated to secondary school for a long time. As the English language is getting stronger influence in the modern world and has become an international language, also, the advantages of introducing a foreign language for young learners, the government of Indonesia then has set up the policy to introduce English language in primary schools. This policy is optional. It depends on schools and community demands. The government does not provide teachers and curriculum. Schools and community are in charge to provide teachers, curriculum and facilities. Teachers are one of the most important parts in the discourse of education and the process of teaching and learning in schools. Furthermore, there are some important considerations before conducting the programs since young children have specific characteristics. It was this that interested me to write a research about some considerations of English language teaching for primary students. Abstrak Pemerintah Indonesia mengakui bahwa bahasa Inggris sangat penting dalam sistim pendidikan yang telah berlangsung selama kurun waktu lima tahun terakhir. Bahasa Inggris sudah beritegrasi ke sekolah-kesekolah sampai tingkat atas dalam waktu yang sudah lama. Selama ini bahasa Inggris memiliki pengaruh yang sangat kuat dalam dunia modern dan menjadi salah satu alat komunkasi yang sangat penting dalam hubungan internasional, juga sangat memberikan keuntungan bagi para pelajar dan generasi muda. Dalam hal ini pemerintah Indonesia kemudian diharapkan memberi kebijakan tersebut untuk mengenalkan pelajaran bahasa Inggris di Sekolah-sekolah Dasar. Kebijakan ini merupakan tambahan di Sekolah dan sangat diminati oleh masyarakat. Pemerintah tidak mesti harus mencetak guru-guru dan menyediakan kurikulum tersebut. Tetapi sekolah dan masyarakat termasuk para guru mesti yang menyediakan kurikulum dan fasilitas tersebut. Para guru adalah salah satu bagian pokok penting dalam memberikan proses pendidikan dan pengajaran di Sekolah. Lagipula, ada beberapa pertimbangan-pertimbangan penting sebelum melaksanakan program itu karena umumnya generasi muda sangat membutuhkan karakter yang sangat spesifik. Untuk itulah saya sangat tertarik meneliti beberapa pertimbangan-pertibambangan tentang perlunya pengajaran bahasa Inggris kepada Generasi Muda.